(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article provides experimental data from immunological studies conducted on mice regarding the formation of antibodies. Тhe results obtained allow us to establish the maximum accumulation of antibodies. It has been shown that the circulation of specific antibodies is maintained at a detectablee level. We can conclude that the most significant for diagnising the use of psychotropic substances is the identification of class antibodies JgM